SOME ASPECTS REGARDING THE GENETIC AND BIOTECHNOLOGICAL PROGRESS OF THE HELIANTHUS ANNUUS L. - Elena BONCIU; Olimpia PANDIA; Aurel Liviu OLARU; Ion SARACIN; Elena ROSCULETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The genetic and biotechnological progress of the Helianthus annuus L. (sunflower) it can be catalogued through two major directions, namely: tissue culture and meristems in vitro, for the induction and selection of useful characters and genetic engineering or DNA manipulation, for plants transformation. In general, sunflower tissues are very easy to grow, but the problem arises due to the low reproducibility, sunflower being one of the most difficult species from this point of view. The two methods of the vitrocultivated sunflower regeneration are organogenesis and embryogenesis, the difference between them being given by the different number of cells from which the neoplants are formed. To date, a limited number of sunflower genotypes have been found for regeneration. For this reason, several methods are sought for the regeneration of this plant, as it is a necessity to find new, stronger genotypes that adapt to the current conditions. From this point of view, the use for vitroculture of tissues initiated from immature sunflower embryos is an effective strategy for plant regeneration. So far, good results have been obtained in the reproductive genetics of this plant but other future results are being sought, when it is expected that genetic and biotechnological progress will continue. One of the basic research methods of genetics and genetic engineering remains the study of gene expression and the elucidation of new aspects at the genome level of the species H. annuus.